Metody i techniki wspomagające zarządzanie projektami w przedsiębiorstwie - Szozda, Natalia; Wąsowicz, Marek (Methods and techniques support project management in enterprises, 2006)
In article authors introduced tire most popular methods and technique supported management projects. In their opinion evolution will proceeded in direction complex computer systems, which will use many methods and techniques, to cause project management more effective.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 316-322